Pengaruh Brand Ambassador Dan Advertising Terhadap Keputusan Pembelian Smartphone Xiaomi - Bagus Sanjaya; M. Ilham muddin; Rus minah (Journal of Sharia Economy and Islamic Tourism, 2022)
Abstract: This research was conducted to test the influence of Brand Ambassador and Advertising on Xiaomi smartphone purchase decisions. This type of research is associative with a quantitative approach. The population in this study was all students of Mataram University. The number of samples used in this study was 100 people using the survey method. The data collection techniques used are observation, questionnaire / questionnaire and online survey by disseminating questionnaires through google form that contains statements about Brand Ambasssador, Advertising and Purchasing Decisions. The data analysis tool used is the Hypothesis Test which is the t test and f test using the SPSS 25 for windows program. The results of the t test analysis showed that there was a positive influence and significance of the Brand Ambassador (X1) on the Purchase(Y) decision with a thitung> ttabel (2,003 > 1.9847) and a significance level of 0.048 less than the standard level of significance of 0.050. And the positive influence and significance of Advertising (X2) on purchasing decisions (Y) with a value of thitung> ttabel (2.054 > 1.9847) and a significance level of 0.043 is smaller than the standard level of significance of 0.050.Abstrak: Penelitian ini dilakukan untuk menguji pengaruh Brand Ambassador dan Advertising terhadap keputusan Pembelian smartphone Xiaomi. Jenis penelitian ini adalah asosiatif dengan pendekatan kuantitatif. Populasi dalam penelitian ini adalah seluruh mahasiswa Universitas Mataram. Jumlah sampel yang digunakan dalam penelitian ini adalah 100 orang dengan menggunakan metode survey. Teknik pengumpulan data yang digunakan adalah observasi, angket/kuisioner dan online survey dengan menyebarkan kuisioner melalui google form yang berisi pernyataan tentang Brand Ambasssador, Advertising dan Keputusan Pembelian. Alat analisis data yang digunakan adalah Uji Hipotesis yaitu uji t dan uji f dengan menggunakan program SPSS 25 for windows. Hasil analisis uji t menunjukkan bahwa ada pengaruh positif dan signifikansi Brand Ambassador (X1) terhadap keputusan Pembelian(Y) dengan nilai thitung> ttabel (2,003 > 1,9847) dan tingkat signifikansi 0,048 lebih kecil dari taraf standar signifikansi 0,050. Dan pengaruh positif dan signifikansi Advertising (X2) terhadap keputusan Pembelian (Y) dengan nilai thitung> ttabel (2,054 > 1,9847) dan tingkat signifikansi 0,043 lebih kecil dari taraf standar signifikansi 0,050.